Robust Imidazole‐15N2 Synthesis for High‐Resolution Low‐Field (0.05 T) 15N Hyperpolarized NMR Spectroscopy. Issue 16 (1st June 2017) - Shchepin, Roman V.; Barskiy, Danila A.; Coffey, Aaron M.; Feldman, Matthew A.; Kovtunova, Larisa M.; Bukhtiyarov, Valerii I.; Kovtunov, Kirill V.; Goodson, Boyd M.; Koptyug, Igor V.; Chekmenev, Eduard Y.
Abstract: NMR hyperpolarization techniques have the potential to revolutionize the field of NMR spectroscopy and molecular MRI because they can transiently enhance nuclear spin polarization by 4–8 orders of magnitude, with corresponding gains in NMR signal‐to‐noise ratio (SNR). The SABRE‐SHEATH (Signal Amplification By Reversible Exchange in SHield Enables Alignment Transfer to Heteronuclei) technique, first demonstrated in 2015, allows for direct, efficient (>20 % nuclear spin polarization), and fast (in under one minute) hyperpolarization of 15 N sites. Several classes of biologically relevant 15 N hyperpolarized contrast agents have been efficiently hyperpolarized to date including pH sensors, which can be potentially useful for non‐invasive pH imaging of cancer and other diseases with altered metabolism. Here, we report the optimized 15 N enrichment of imidazole‐ 15 N2 – a promising in vivo pH sensor with pKa ∼ 7.0. A hyperpolarized 0.1 M aqueous solution (ϵ15N ∼ 146, 000 fold, P 15N ∼ 0.24 %) was used to record 15 N NMR spectra at 0.05 T, demonstrating the feasibility of high‐resolution (full width at half maximum ∼ 1 Hz corresponding to 5 ppm at 0.05 T) NMR spectroscopy near its pKa (7.0) at ultra‐low magnetic field. Given that proton‐binding events modulate the chemical shift by ∼ 30 ppm for this pH‐sensing probe, our results demonstrate the feasibility of ultra‐low‐field pH sensing near its pKa (7.0) with SNR approaching that of high‐field (9.4 T) MR. Abstract : Robust synthesis of 15 N enriched imidazole‐ 15 N2 is reported for 15 N hyperpolarization using parahydrogen gas. High‐resolution 15 N NMR spectroscopy of this promising pH sensor is demonstrated at 0.05 T.